Do Late Season Soybean Management Practices Impact Seed Yields in East Kansas? - A. A. Correndo; L. F. A. Almeida; E. Adee; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2022)
In soybean (Glycine max[L.] Merr.), maintaining favorable growth conditions (e.g., water, solar radiation, and nutrients) during the seed filling period is crucial to avoid limitations that could reduce seed weight and ultimately constrain seed yield. The objective of this study was to explore potential effects and identify if “late-season” management practices can contribute to increasing seed weight and seed yield in soybeans.
Keywords: Crop productivity; yield gap; inoculation; fertilization; crop protection; soybean